2014
DOI: 10.1111/sode.12089
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Institutionalization and Foster Care Intervention on Children's Social Behaviors at the Age of Eight

Abstract: The present study compared the social behaviors of 8-year-old previously institutionalized Romanian children from the Bucharest Early Intervention Project (BEIP) in two groups: 1) children randomized to foster care homes (FCG), and 2) children randomized to care as usual (remaining in institutions) (CAUG). Children were observed interacting with an age and gender-matched unfamiliar, non-institutionalized peer from the community (NIG) during six interactive tasks, and their behavior was coded for speech reticen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 31 publications
5
49
0
8
Order By: Relevance
“…Nonetheless, the behavioral results were consistent with Almas et al () who found no differences between the institutionalized group and the foster care intervention group except for speech reticence, a variable not measured here. Because the studies who typically find social behavior differences between post‐institutionalized and non‐adopted children at this age tend to assess the quality of relationships with familiar peers and close friends (e.g., Gunnar et al, ; Roy et al, ; Tieman et al, ), there may be subtle differences between post‐institutionalized and non‐adopted children that are not distinguishable by the present study's observational design but are noticed by the people interacting with them on a daily basis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, the behavioral results were consistent with Almas et al () who found no differences between the institutionalized group and the foster care intervention group except for speech reticence, a variable not measured here. Because the studies who typically find social behavior differences between post‐institutionalized and non‐adopted children at this age tend to assess the quality of relationships with familiar peers and close friends (e.g., Gunnar et al, ; Roy et al, ; Tieman et al, ), there may be subtle differences between post‐institutionalized and non‐adopted children that are not distinguishable by the present study's observational design but are noticed by the people interacting with them on a daily basis.…”
Section: Discussionsupporting
confidence: 90%
“…In the absence of a direct effect of institutionalization on peer's behavior and cortisol during the dyadic interaction, and with consideration of the results in Almas et al () described above, we conducted post‐hoc analyses to explore whether there might be moderating effects of group (post‐institutionalized vs. non‐adopted) such that the association between “target” and “peer” behavior and cortisol might be different when the target is a post‐institutionalized child versus a non‐adopted child. Consistent with the analyses in Almas et al (), we used an Actor‐Partner Interdependence Model (APIM) to examine dyadic influences of interaction quality and affect from one task, Etch‐a‐sketch, to the next, Simon (see Figure for conceptual model; Cook & Kenney, ). This model allows us to examine the impact of target children's behavior on peers’ behavior and cortisol, moderated by group, while controlling for the converse (the impact of peers’ behavior on target children's behavior and cortisol, moderated by group).…”
Section: Resultsmentioning
confidence: 99%
“…Beginning in early childhood, positive peer interactions and later the establishment of peer friendships become critical developmental tasks (Hartup & Moore, ), which predict later psychological and behavioral adjustment (e.g., Reijntjes, Kamphuis, Prinzie, & Telch, ). PI youth, especially those who have experienced longer durations of adverse care, are reported to experience more social problems (e.g., Gunnar, van Dulmen, & International Adoption Project Team, ; Hawk & McCall, ; Pitula et al., ) including difficulties forming and maintaining friends (Almas et al., ; Hodges & Tizard, ). However, very little is known about the peer relationships of PI adoptees in early childhood, particularly using observational instruments rather than parental report.…”
Section: Peer Relationship Functioning In Pi Youthmentioning
confidence: 99%
“…FCG children also demonstrated an attention bias to positive facial expressions of emotion at both 8 and 12 years [30, 31]. Social behaviors, including peer relations and social skills were enhanced [32, 33]. Externalizing signs, CU traits and attachment disorder behaviors at 12 years all were reduced for children living in foster care [3437].…”
Section: Discussionmentioning
confidence: 99%
“…Secure attachments at 42 months, which were significantly more likely in children in foster care, mediated the effect of caregiving quality on psychopathology at 54 months [46]. In fact, secure attachment in early childhood also predicted other subsequent outcomes, including IQ and peer relations at 8 years [26, 47]. …”
Section: Keys To the Success Of The Interventionmentioning
confidence: 99%